Conversation Analysis: Turn-Taking Analysis in Variety’s Actors on Actors Conversation Video featuring Zendaya and Andrew Garfield - Noval, Ahmad Yazid; Athallah, Aufa Tsabitah; Pujiati, Hanip (STAIRS: English Language Education Journal, 2022)
This study is proposed to analyze conversation analysis, especially for turn-taking strategy in a video of Actors on Actors Conversation by Variety featuring Zendaya and Andrew Garfield. This study used a qualitative method with Stenstrom’s framework to analyze the turn-taking strategy used in the conversation. The process of analysis consists of four steps; streaming Variety’s Actors on Actors Conversation video featuring Zendaya and Andrew Garfield, transcribing the conversation, classifying the data, and interpreting the data. The result of this study showed that turn-taking strategies appear in the conversation. There were starting up, promoting, interrupting, repeating words, taking over, overlapping, appealing, silent pauses, and filled pauses. The most frequent turn-taking strategy used is the overlapping strategy. Therefore, this study suggests that conversation analysis is important for understanding the intent of people's speech. In addition, this study can be used as a reflection on both theoretical and practical contributions. In theory, this study supports the theory of conversation analysis in turn-taking strategies. In fact, teachers can use it as a reference for applied linguistics courses.